2018
DOI: 10.1021/acs.jced.8b00680
|View full text |Cite
|
Sign up to set email alerts
|

Low-Pressure VLE Measurements and Thermodynamic Modeling, with PSRK and NRTL, of Binary 1-Alcohol + n-Alkane Systems

Abstract: New subatmospheric vapor−liquid equilibrium (VLE) data for five binary 1-alcohol + n-alkane systems are presented. An all-glass dynamic recirculating still was used to measure the phase behavior of the 1-pentanol + n-nonane, 1-hexanol + n-decane, 1-heptanol + n-undecane, 1-octanol + n-dodecane, and 1-decanol + n-tetradecane systems at 40 kPa. Each of the five systems displayed an azeotrope, indicating complex molecular interactions. Thermodynamic modeling was conducted with (1) the NRTL activity coefficient mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(45 citation statements)
references
References 46 publications
7
38
0
Order By: Relevance
“…In order to better understand the complex phase behavior and improve the thermodynamic modeling for these systems, phase behavior data are required for the 1-alcohol + n -alkane systems. Hence, a previous study considered the low-pressure fluid phase behavior for binary systems of 1-alcohols + n -alkanes, where the n -alkane had four more carbon atoms than the 1-alcohol . Since the measurement of data for molecules larger than 1-decanol and n -tetradecane are difficult due to the high boiling points observed, lower boiling combinations were considered, with the hope of extrapolating the trends observed to the higher boiling homologues by means of predictive thermodynamic models.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand the complex phase behavior and improve the thermodynamic modeling for these systems, phase behavior data are required for the 1-alcohol + n -alkane systems. Hence, a previous study considered the low-pressure fluid phase behavior for binary systems of 1-alcohols + n -alkanes, where the n -alkane had four more carbon atoms than the 1-alcohol . Since the measurement of data for molecules larger than 1-decanol and n -tetradecane are difficult due to the high boiling points observed, lower boiling combinations were considered, with the hope of extrapolating the trends observed to the higher boiling homologues by means of predictive thermodynamic models.…”
Section: Introductionmentioning
confidence: 99%
“…For systems of type n -paraffin + 1-alcohol, Ferreira and Schwarz measured isobaric PTxy data for five mixtures of this type at 40 kPa, including n-dodecane + 1-octanol (system 11). They showed that azeotropic points were present in all mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…System 8: 1-decanol (1) + 1-dodecanol (2) at 4.97 kPa. This work (●); 2.67 kPa (■); 6.67 kPa (▲); ideal (−).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations